INDONESIA AND THE ASEAN ECONOMIC COMMUNITY: A TUSSLE BETWEEN HUMAN AND CULTURE IN THE REGIONAL MATERIALISM SUBLIMATION - Setiawan, Topan (ADDIN, 2016)
This study aimed to feel the subtle vibrations of a “project” of the ASEAN Economic Community (AEC), the human dimension and its culture. However AEC becomes part of the life history of the nations of Southeast Asia, particularly in the visible measures, such as economic growth, the economic stability of the region or the increasing of intra-regional trade volume. It means, that we feel it in the materialist dimension, or “vibrations” a “rough”. Besides, this study attempted to feel the euphoria of the other aspects. This paper will track a bit more deeply about Indonesian and its culture. Also there will be an effort to seek traces (perhaps disguised) in regional sublimation materialism “project” by AEC. Strive to be this insight led to the discovery that regional sublimation Reviews their materialism, for the next attempt to pave the way consciousness. Also, how sublimation material, it is not exactly cornered people and cultures. Another invention is the reification of culture, which it is the manifestation, in the form of Materialization on social relations, by considering it as a thing freely. Similarly, it is forgetting the historical trail of goods/services. Search back on local wisdom, seems to be one way that can be taken.